(3GdCQHYhf aj CUhd GdOjfs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s ((3UOjb Hf CMeO Hf UOjb Hf CHj fUQ GdgePGfi s)
(3ChdgG (B:s
(3bGd ehdGfG aNQ GdOjf GdQGRi SHMGf GdeJaQO ai bjeheJg HhLhH GdCRdjI hGdHbGA CeG HYO aEf Gddg JYGdi deG habi Mi Ufa ai CcKQ GdYdhe s
(3BNQgG (B:s
(3hGdeYQcI GdcHQi hGdWGeI GdYXei ai gPG GdehVhY gi ebOeI GdhLhH hGdEecGf hHGddg GdJhajb hgPG BNQ GdcJGH hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HBNQgG agQSJ deSGFd GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B79s
Keywords: (3GdJhMjO hGdedd hGdfMds